Structural and in vivo studies of metal chelates of Ga(III) relevant to biomedical imaging - Prata, M. I. M. (2000)
The solution chemistry and structure of the complex of the triazamacrocyclic ligand NOTP (1,4,7-triazacyclononane-1,4,7-tris(methylenephosphonate)) with Ga3+ in D2O have been investigated by 1H, 71Ga and 31P NMR spectroscopy. These NMR results show the presence of a 1:1 Ga(NOTP)3- complex, with a highly symmetrical, pseudo-octahedral geometry, possibly with a C3 axis. The 1H spectrum shows that the triazamacrocyclic chelate ring is very rigid, with all the ring protons non-equivalent. The complex is stable in aqueous solution in a wide pH range. Its high thermodynamic stability agrees well with previous results from biodistribution and [gamma] imaging studies in Wistar rats with 67Ga3+ chelates of triaza macrocyclic ligands, which showed that the neutral chelates 67Ga(NOTA) (where NOTA is 1,4,7-triazacyclononane-1,4,7-triacetate) and 67Ga(NOTPME) (where NOTPME is 1,4,7-triazacyclononane-1,4,7-tris(methylenephosphonate monoethylester)) have similar in vivo behaviour, with high stability and rapid renal excretion, but the high negatively charged 67Ga(NOTP)3- has a considerably slower kidney uptake and elimination.